PERCEPTION ON HALAL TRACEABILITY ON CHICKEN MEAT SUPPLY CHAIN - Tian Nur Ma'rifat (Universitas Darussalam Gontor, 2017)
Halal is a major requirement for Muslim consumers in consuming food products. Halal traceability is very important because it is useful in responding the potential risk of haram substances contamination that can arise in food. This research was conducted in Region of Ponorogo, Indonesia. With the large number of schools focusing on Islamic Education, the community has a high level of awareness and knowledge about halal food, so that halal traceability is needed for food that consumed by people in region of Ponorogo. The purpose of this research are : (1) describe chicken meat supply chain, (2) analyse the perception of producers and consumers in applying halal traceability in Region of Ponorogo. The research method is field survey to know the condition of supply chain. Interview technique is also applied for supply chains’ actors in eight districts to find out how far the application and perception of supply chain actors toward halal traceability. The results show that chicken supply chain in Ponorogo consists of chicken farmers as a supplier. Chickens live bought by distributors to be sold to chicken meat seller. Then the seller slaughters chicken live and sell them to the market as carcass. Consumer of chicken carcass is household, chicken meat distributor or a restaurant. There is no chicken slaughterhouse that has been halal certified. Merchant’s intention to record and document information about the materials is low. The knowledge of supply chain actors on the ‘Safe, Health, Wholesome and Halal’ status of chicken meat is still low. In addition, there is no clear information about the status of ‘Safe, Health, Wholesome and Halal’ that sellers show to consumers. It can be concluded that the application of traceability in the chicken meat supply chain and the perception of supply chain actors toward it in Ponorogo is still low.